ASSESSMENT OF FACTORS AFFECTING WORK-LIFE BALANCE (WLB) OF WOMEN IT PROFESSIONALS: AN EMPIRICAL STUDY - M. B. Jyothi; D. V. Ramana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article presents findings on the factors affecting the work-life balance of women working in the Information Technology (IT) sector. The information was gathered from 100 respondents selected through a convenience sampling method. These respondents are women IT professionals working in various organizations in Bengaluru city. A total of five hypotheses were formulated for the study to examine the correlation between these factors and work-life balance. Spearman’s rho correlation test was conducted using SPSS software to analyze the correlation between the factors and work-life balance. The results convey that, for Hypothesis 1, (H1) alternative hypothesis is accepted, signifying that there is a significant positive relationship between family responsibilities and work-life balance. In Hypothesis 2- (H1) alternative hypothesis is accepted, indicating that there is a weak but statistically positive relationship between family members’ support and their Work-Life balance. In Hypothesis 3- (H1) Alternative hypothesis is accepted, suggesting that the Current position in the organization significantly affects work-life balance negatively. In Hypothesis 4- (H1) alternative hypothesis is accepted, indicating that there is a strong positive relationship between Overtime work and work-life balance. In Hypothesis 5- (H1) alternative hypothesis is accepted, showing that there is a strong positive relationship between Commute time and work-life balance. All these factors are significantly correlated with the work-life balance of Women in the IT sector.